The purified 14-kilodalton envelope protein of vaccinia virus produced in Escherichia coli induces virus immunity in animals. - Lai, C F (J Virol, 1991)
Vaccinia virus (VV) was successfully used as a live vaccine to eradicate smallpox, but the nature of viral proteins involved in eliciting viral immunity has not yet been identified. A potential candidate is a 14-kDa VV envelope protein that is involved in virus penetration at the level of virus-cell fusion, in cell-cell fusion late in infection, and in virus dissemination. The 14-kDa envelope protein has been produced in Escherichia coli, with properties similar to those of the native protein found in the virus particle and in infected cells (C. Lai, S. Gong, and M. Esteban, J. Biol. Chem. 256:22174-22180, 1990). In this investigation, we showed that mice immunized with purified VV 14-kDa protein synthesized in E. coli in the form of a monomer or a trimer develop high-titer neutralizing antibodies and are protected when challenged with lethal doses of wild-type VV. Our findings demonstrate that it is possible to confer protection against VV through immunization with the 14-kDa envelope protein. IMAGES: